PENGARUH LINGKUNGAN KELUARGA TERHADAP KEMAMPUAN BERBAHASA INDONESIA ANAK USIA 5-6 TAHUN DI TK DESA SUNGAI PINANG KABUPATEN KUANTAN SINGINGI - Umaira, Wardatul; Zulkifli N, Zulkifli N; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the results of field observations, the Indonesian language ability of the students have not developed optimally. Kindergarten children are in an expressive language development phase. This means the child can express his or her desires, rejection, or opinion by using spoken language. The phenomenon that occurs such as follows: (1) Children who daily use the local language, (2) Children who say rude and disrespectful words, (3) Children who do not understand the teachers instructions, (4) The children are difficult to tell their own language about the experience of an event that happened, (5) The children find it difficult to answer the question of what, how, where, why, and how, (6) parents and family members who use the local language as a colloquial language, (7) Parents who do not invite children to communicate with the good Indonesian language, (8) Parents who are too busy with their business so they do not communicate much with children, (9) Parents who do not discipline children in playing and watching television so that the impact on the childs language. The aim of this research is to find out the influence of family environment on the Indonesian language ability towards children aged 5-6. This research uses the form of quantitative research using correlation technique. The data collection in this study uses observation sheet and interview. The sample in the study is about 40 children. Data analysis using simple regression or regresi sederhana. The result of The research shows that the family environment is 60,36% which is categorized good enough and the Indonesian language ability of children is 45,81% which is less good category. From the data analysis, obtained fcalculated = 87.416 and ftable = 2.021 then Ho is rejected. This means that there is an influence of family environment to the Indonesian language ability towards children aged 5-6 years in kindergarten at Sungai Pinang Village, Kuantan Singingi Regency.Key Words: Family environment, Indonesian language ability